Justice in the Perspective of the Qur'an and the Sacred Texts of Other Religions and its Contextuality - Hubby Dzikrillah Alfani, Ilzam; Mukhsin, Mukhsin; Sutisna, Nata (FALASIFA : Jurnal Studi Keislaman, 2024)
This paper explores the views of various religions on justice as a value that must be upheld because it pertains to the well-being of life. The purpose is to broaden the understanding of interfaith ideologies in Indonesia. This research employs a qualitative approach, relying on literature studies analyzed descriptively. The paper concludes that there are several perspectives on the definition of justice. According to Islam, justice is divided into three forms: first, justice in a material and immaterial sense, closely related to fulfilling rights and obligations among all beings. Second, justice in the form of balance, meaning impartiality towards oneself, relatives, and those of the same faith. Third, justice as retribution, signifying the consequences of one's actions. In Christianity, the term "tsedeq" refers to righteousness, associated with God’s justice in His covenant to sustain, save, and act against His people's enemies. In Hinduism, as presented in the Vedas, justice is a trait of actions and behavior. God bestows justice evenly upon all beings, allowing them to act and liberate themselves from samsara (repeated birth) as a result of their deeds. In Buddhism, according to the Tripitaka, justice refers to the potential and virtues within humans, which are inherently unbound by the physical body. In Confucianism, as taught in the Si Shu, justice is viewed as equality that must be upheld. The goal in Confucian teachings is to cultivate virtuous, loving, truthful, just, dutiful, wise, and trustworthy individuals